The yurt and its details in Tuvan riddles - Bochina , Tatyana G. (The New Research of Tuva, 2024)
The article analyzes the linguistic and cultural features of Tuvan riddles related to felt yurts. The study focuses on Tuvan riddles related to artifacts in their enigmatic function (objects of reality encoded in riddles). The source for the study was a collection of Tuvan riddles compiled by G. N. Kurbatsky, from which 297 riddles were selected using continuous sampling method. Ratings of the thematic groups and frequency of riddles have been compiled. Based on the findings, the mysteries of the yurt occupy prominent positions in this context. It has been demonstrated that the yurt and its various parts are encoded through a series of riddles, which are embedded within the archetypal oppositions of “top — bottom”, “outside — inside”, “open — closed”, “moving — stationary”, and “animate — inanimate”. At the same time, anthropomorphic, zoomorphic, and biomorphic cultural codes are often used to metaphorically describe artifacts, in other words, objects are described through the metaphorization of natural phenomena.